INVENTARISASI TUMBUHAN FAMILI ZINGIBERACEAE DI KAWASAN GUNUNG SIBUATAN KECAMATAN MEREK KABUPATEN KARO SUMATERA UTARA - Shofura Rufaida; Husnarika Febriani; Melfa Aisyah Hutasuhut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The study aims to identify and determine the characteristics of plants based on the key to determining Zingiberaceae plants in Mount Sibuatan, Nagalingga village, Brand district, Karo district, North Sumatra. The research was conducted from November 2020 to May 2021.The research method used a qualitative descriptive method by exploratory observations along the path starting from the jungle door up to altitude 1500 mdpl. The results showed 15 species of Zingiberaceae, namely Amomum lappaceum Ridl, Etlingera elatior (Jack) R.M. Sm, Etlingera sp.1, Etlingera sp.2, Etlingera sp.3, Geostachys decurvata (Baker) Ridl, Globba marantina L, Globba paniculata Valeton, Globba patens Miq, Globba pendula Roxb, Globba sp, Hedycium sp, Hornsteditia scyphifera (J . Koening) Steud, Zingber zerumbet (L.) Roscoe ex Sm, and Zingiber sp.